Religious Moderation in Indonesia: A Study on Implementation Patterns of the Indonesian Ulema Council (MUI) - Pagar Pagar; Syaiful Akhyar; Ibnu Radwan Siddik Tunip (Faculty of Law, Universitas Pekalongan, 2023)
As a symbol of ulema which is the main tent of Muslims in Indonesia, the Indonesian Ulema Council (MUI) is certainly expected to be able to implement the concept of religious moderation. This paper aims to examine the implementation of MUI religious moderation in Indonesia. Then, this study also aims to discuss how the pattern of implementation of MUI religious moderation towards Muslims, deviant religious beliefs, non-Muslims, and the government. This is qualitative research with a participatory action research (PAR) approach. Informants involved as subjects and objects in this study were structural scholars, academic scholars, and community scholars in the provinces of DKI Jakarta, North Sumatra, and Aceh. The results of the study indicate that the implementation of MUI religious moderation in Indonesia has been implemented well. MUI is responsive and accommodating to the needs of the community, especially Muslims, and plays a very important role in creating a safe and peaceful atmosphere in the community. However, some people consider that the application of MUI's religious moderation values to groups that are considered deviant (heretic) and non-Muslims has not run optimally. This can be seen with the issuance of the MUI fatwa on the expectation of the existence of pluralism, liberalism, and religious secularism. MUI is expected to further improve the pattern of its relationship with the two community groups. Meanwhile, towards the government, MUI positions itself as a critical partner of the government (syarikatul hukumah). MUI sometimes supports government programs, but it can also disagree with government programs as outlined through MUI fatwas that seem contrary to the interests of the government,such as fatwas against vasectomy and fatwas on the use of meningitis vaccines for pilgrims or umrah.